Intersubjektivnost i refleksivnost u vizualnoj antropologiji: uporaba video kamere u intervjuima usmene povijesti - Bukovčan Žufika, Tanja (2003)
The article adresses new fieldwork methodologies in ethnology and cultural anthropology. It specifically deals with oral history and the ways of conducting open interviews by the means of video camera.